Anxiety and Depression in Patients with Primary Biliary Cholangitis: Current Insights and Impact on Quality of Life - Sivakumar T (Hepatic Medicine : Evidence and Research, 2021)
Tarika Sivakumar, Kris V Kowdley Liver Institute Northwest Seattle, Seattle, WA, USACorrespondence: Kris V KowdleyLiver Institute Northwest, 3216 NE 45th Pl, Suite 212, Seattle, WA, 98105, Tel +1 206-536-3030Fax +1 206-524-0749Email kkowdley@liverinstitutenw.orgAbstract: Primary biliary cholangitis (PBC), formerly known as primary biliary cirrhosis, is a chronic cholestatic immune-mediated liver disease characterized by injury to intrahepatic bile ducts that may ultimately progress to cirrhosis and liver failure and result in the need for liver transplant or death without treatment. Ursodeoxycholic acid (UDCA) and obeticholic acid (OCA) are approved therapies for PBC and are associated with a reduced risk of progression of disease, although patients may continue to experience significant symptoms of pruritus and fatigue independent of liver disease. The two most commonly reported symptoms among patients with PBC are fatigue and pruritus which may be debilitating, and negatively impact physical, mental, emotional, and social wellbeing. Intense symptom burden has been associated with depressive symptoms, cognitive defects, poor sleep schedules, and social isolation. This literature review explores the presence of anxiety and depressive symptoms in chronic liver disease, the impact of symptom burden on patients’ wellbeing, and available pharmaceutical and natural therapies.Keywords: primary biliary cholangitis, depression, anxiety, fatigue, quality of life, chronic liver disease